High Framingham risk score decreases quality of life in adults - Yosaputra, Christian; Kholinne, Erica; Taufik, Erick Susanto (Universa Medicina, 2010)
Cardiovascular disease (CVD) risk factors, such as diabetes, hypertension, hypercholesterolemia,Â  smoking, and obesity tend to occur together in the general population. Increasing prevalence of multiple CVD risk factors has been related to increased risk of death from coronary heart disease and stroke. Studies have suggested that people with several risk factors of CVD may have impaired health-related quality of life. The objective of this study was to assess the association of CVD risk factors with quality of life (QOL) among adults aged 40 to 65 years. A cross-sectional study was conducted involvingÂ  220 subjects 40 - 65 years of age at a health center. The CVD risk factors were assessed using the Framingham risk score that is the standard instrument for assessment of the risk of a first cardiac event. The risk factors assessed were age, smoking, blood pressure, total cholesterol and high density lipoprotein cholesterol concentrations. QOL was assessed by means of the WHOQOL-BREF instrument that had been prevalidated. The results of the study showed that 28.2% of subjects were smokers, 56.4% had stage 1 hypertension, 42.8% high total cholesterol and 13.6% low HDL cholesterol. The high risk group amounted to 45.5% and 42.3% constitued an intermediate risk group. High CVD risk scores were significantly associated with a low QOL for all domains (physical, psychological, social and environment) (p=0.000). Preventing or reducing the multiple CVD risk factors to improve QOL is necessary among adults.